Effect of tannins of Albizia lebbekoides on the in vitro fermentation of star grass (Cynodon nlemfuensis) during the dry season - Rodr?guez, Rafael; Alfonso, Dagoberto; Oramas, A.; Hern?ndez, Y. (Cuban Journal of Agricultural Science, 2010)
The in vitro gas production, up to 72 h, the kinetic parameters of fermentation according to the model Y= D*1-Exp [-C*(Hour-L)], and the non-fermented residue for estimating the apparent degradability of dry matter were determined to evaluate the effect of the tannins from the tree legume A. lebbekoides on the in vitro fermentation of star grass (C. nlemfuensis) when using supplement for the dry season. A completely randomized design with factorial fit (4 x 2) was used, where the A factor was the diet assessed; star grass (100 %), albizia (100 %), star grass + albizia (15 %), and star grass + albizia (30 %) and the B factor was the inclusion of polyethyleneglycol to inactivate the tannins for having a total of eight treatments. The fermentation of the forages showed that since 12 h the gas production of star grass was higher than that of the legume (P < 0.05). However, in the treatments mixing the two plant species, the gas production was not affected in respect to star grass, except between 12 and 24 h of incubation for the 30 % inclusion level. The potential of gas production of albizia (38.7 mL) was much lower than that of star grass (88.4 mL) and by increasing the inclusion level of legume, the potential and the fractional rate of gas production of the diet were reduced. The lag phase showed a trend to decline, as the inclusion level of the legume was increased (from 40.1 for star grass to 32.3 in star grass + albizia 30 %). The apparent degradability of dry matter diminished as the inclusion level of th legume was increased. It is concluded that the two inclusion levels of Albizia lebbekoides did not affect the fermentation of the basic diet of Cynodon nlemfuensis, except the 30 % level between 12 and 24 h of incubation. However, the potential kinetic indicators of gas production, the fractional rate, and the lag phase were indeed affected. The tannins affected the gas production and influenced on the kinetic parameters of fermentation. Key words: Albizia lebbekoides, Cynodon nlemfuensis, gas production, tannins.